Preparation and application of an OP bidentate fifth subgroup pentavalent metal complex
By preparing the fifth -valent metal mathematical object of the OP diothy, the existing catalysts have been solved in terms of structural modification, purity, structural regulation, high temperature tolerance, long life, low cost and catalytic performance. The effect of ethylene and multiple concentration reactions.
Patent Information
- Application Number
- CN202410677925.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-05-29
AI Technical Summary
The existing olefin polymerization catalysts have shortcomings in structural modification, purification, structural regulation, high temperature tolerance, long life, low cost and catalytic performance, which are difficult to meet the needs of industrial production.
Prepare an OP bidentate fifth subgroup pentavalent metal complex. Through reasonable modification design, the obtained catalyst has low cocatalyst usage, high catalytic activity, good thermal stability, long life and low cost, and can Efficiently catalyzes the copolymerization of ethylene and cyclic olefins, and ethylene and polar monomers.
The catalyst structure is easy to modify and control, has a simple synthesis route, is convenient for purification, has high catalytic activity, good thermal stability, and long service life. It can effectively catalyze a variety of copolymerization reactions and obtain high-quality polymers.
Smart Images

Figure CN118598909B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of olefin polymerization catalysts, and in particular relates to the preparation and application of an OP bidentate fifth subgroup pentavalent metal complex. Background Art
[0002] Polyolefin products have become the most widely used synthetic resin materials in production and life due to their abundant raw materials, low price, easy production and processing, superior performance and many other advantages. The development level of the polyolefin industry directly represents the development level of a country's petrochemical industry and is an important part of the national economy and national defense strategy. Olefin polymerization catalysts directly determine the internal structure and morphology of polyolefin products and are the most core technology in the development of the polyolefin industry. Its development has generally gone through three stages: (a) Ziegler-Natta catalysts, which are the earliest polyolefin catalysts. Their emergence has given birth to the polyolefin industry and made it flourish. However, the structure of this type of catalyst is not easy to modify and the types are relatively single. When used, because the catalyst is heterogeneous, it is difficult to be fully activated by the co-catalyst, and there are problems such as multi-center, low efficiency, and high ash content in the obtained product; in addition, this type of catalyst cannot catalyze the copolymerization of ethylene and α-olefins, and the types of the obtained products are relatively single, which is difficult to meet the actual demand for product diversification. (b) Metallocene catalysts. This type of catalyst basically solves the shortcomings of Ziegler-Natta catalysts and enriches the types of polyolefin products. However, a large amount of expensive co-catalysts (MAO or boron co-catalysts) need to be added during use, which has high use costs and high ash content in the resulting products. At the same time, its active center is easily poisoned and deactivated, which limits its application in industrial production. (c) Non-metallocene catalysts. This type of catalyst has a single active center, relatively high activity, and the central metal has strong tolerance to heteroatoms. It has the advantages of the previous two generations of catalysts and can catalyze the homopolymerization and copolymerization of multiple series of olefin monomers. It can also achieve precise control of the molecular weight and internal morphology of polyolefin products, enriching the types of polyolefin products, and thus has a very broad application prospect.
[0003] Scientists Nomura et al. reported an aryl acyl monoimide vanadium catalyst (Macromolecules 2005, 38, 5905-5913), but the catalyst has a weak ability to catalyze olefin copolymerization and poor high temperature resistance. Li Yuesheng et al. reported an OP bidentate vanadium (III) catalyst (Journal of Polymer Science, Part A: Polymer Chemistry 2012, 50, 4721-4731), which can catalyze the copolymerization of ethylene and ethylene with α-olefins, but due to the paramagnetism of trivalent vanadium, it cannot be tested by nuclear magnetic resonance, which is not conducive to structural characterization, and when it catalyzes the copolymerization of ethylene and α-olefins, the comonomer insertion rate in the obtained polymer is low.
[0004] Therefore, it is of great significance to change the structure of existing catalysts and design a catalyst that is simple to synthesize, convenient to purify, easy to characterize, easy to regulate the structure, has good high temperature tolerance, long life, low cost and excellent catalytic performance. Summary of the invention
[0005] The invention provides preparation and application of an OP bidentate fifth subgroup pentavalent metal complex. After reasonable modification, the prepared catalyst has the advantages of low usage of co-catalyst, high catalytic activity, good thermal stability, long service life, etc.; at the same time, the catalyst can also efficiently catalyze the copolymerization reaction of ethylene and cycloolefin, and ethylene and polar monomer.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] An OP bidentate fifth subgroup pentavalent metal complex has the following general structural formula:
[0008]
[0009] Wherein, R1 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, a phenyl group, a phenyl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a triphenylmethyl group;
[0010] R2 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, a phenyl group or a cumyl group;
[0011] R3 is hydrogen, methyl, ethyl, propyl, isopropyl or halogen;
[0012] M is a pentavalent transition metal of the fifth subgroup, vanadium, niobium or tantalum;
[0013] X is halogen, alkyl, silane or benzyl.
[0014] The present invention also provides a method for preparing an OP bidentate fifth subgroup pentavalent metal complex, comprising the following steps:
[0015] Under the catalysis of pyridinium p-toluenesulfonate, phenolic compounds and 3,4-dihydropyran undergo condensation reaction, and the obtained product is post-treated to obtain a white powder;
[0016] In a nitrogen atmosphere, the white powder is added to THF, and the obtained solution is subjected to a metalation reaction with n-butyl lithium to generate a lithiated intermediate; the lithiated intermediate is reacted with diphenylphosphine chloride to form a phosphorus compound, water is added to quench the reaction, and a compound is obtained through post-treatment;
[0017] The compound is dissolved in CH2Cl2, water and concentrated hydrochloric acid are added to perform a hydrolysis reaction, and a ligand is obtained through post-treatment;
[0018] Under an inert atmosphere, a pentavalent transition metal compound of the fifth subgroup is added to dry benzene, and stirred at room temperature to obtain a solution;
[0019] The ligand is added to the solution in the form of powder, triethylamine is added, the mixture is stirred at room temperature, filtered, concentrated, and stirred after adding n-hexane. The precipitated solid is filtered and dried to obtain a metal complex.
[0020] Further, the molar ratio of the pyridinium p-toluenesulfonate, the phenolic compound and 3,4-dihydropyran is 5.6:112:168;
[0021] The molar ratio of the white powder, n-butyl lithium and diphenylphosphine chloride is 34:37.4:39.
[0022] The present invention also provides an application of an OP bidentate fifth subgroup pentavalent metal complex in catalyzing the copolymerization reaction of ethylene and norbornene, wherein the OP bidentate fifth subgroup pentavalent metal complex is used as a main catalyst, and alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as a co-catalyst.
[0023] Further, the molar ratio of the metal in the main catalyst to the aluminum in the co-catalyst is 1:(5-10000);
[0024] The molar ratio of the metal in the main catalyst to the boron in the co-catalyst is 1:(0-2);
[0025] During the copolymerization reaction, the ethylene pressure is 0.1-10 MPa.
[0026] The present invention also provides an application of an OP bidentate fifth subgroup pentavalent metal complex in catalyzing the copolymerization reaction of ethylene and a hydroxyl-containing polar monomer, wherein the OP bidentate fifth subgroup pentavalent metal complex is used as a main catalyst, and an alkylaluminoxane, a modified alkylaluminoxane, a halogenated alkylaluminum, or a mixture of an alkylaluminum and a boron agent is used as a co-catalyst.
[0027] Further, the molar ratio of the metal in the main catalyst to the aluminum in the co-catalyst is 1:(5-10000);
[0028] The molar ratio of the metal in the main catalyst to the boron in the co-catalyst is 1:(0-2);
[0029] During the copolymerization reaction, the ethylene pressure is 0.1-10 MPa.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] 1) The structure of the metal complex of the present invention is easy to modify and regulate;
[0032] 2) The synthesis route and purification method of the metal complex of the present invention are very simple, which is conducive to the realization of scale-up production;
[0033] 3) The catalyst of the present invention has high activity in catalyzing ethylene homopolymerization and can produce highly linear polyethylene;
[0034] 4) The catalyst of the present invention has good temperature resistance and can still maintain good catalytic activity under high temperature conditions;
[0035] 5) The metal center of the catalyst of the present invention is stable and the catalytic life is very long;
[0036] 6) The catalyst of the present invention catalyzes the copolymerization of ethylene and norbornene with high activity and high comonomer insertion rate in the polymer;
[0037] 7) The catalyst of the present invention catalyzes the copolymerization reaction of ethylene and 5-norbornene-2-methanol with high activity, and can obtain functionalized polyolefin products. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0039] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the complex C1 provided in Example 2 of the present invention;
[0040] Figure 2The carbon nuclear magnetic resonance spectrum of the ethylene-norbornene copolymer provided in Application Example 3 of the present invention;
[0041] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the copolymer of ethylene and 5-norbornene-2-methanol provided in Application Example 4 of the present invention. DETAILED DESCRIPTION
[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0043] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] The "room temperature" in the present invention refers to 25°C unless otherwise specified.
[0048] The raw materials used in the present invention are all purchased from the market.
[0049] The metal complex provided by the present invention is used as a main catalyst, and under the activation of a small amount of a co-catalyst, it can catalyze the homopolymerization of ethylene, and has the advantages of high catalytic activity, good thermal stability, long service life, and applicability to a variety of solvent systems; it catalyzes the copolymerization of ethylene and norbornene, and can obtain a polymer product with a high comonomer content with ultra-high activity catalysis; at the same time, the metal complex can also catalyze the copolymerization of ethylene and a hydroxyl-containing polar monomer to obtain a functionalized polyolefin product. The specific technical scheme is as follows:
[0050] An OP bidentate fifth subgroup pentavalent metal complex has the following general structural formula:
[0051]
[0052] Wherein, R1 is an alkyl group containing 1-10 carbon atoms, an alkoxy group containing 1-10 carbon atoms, a phenyl group, a phenyl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a trityl group; R2 is an alkyl group containing 1-10 carbon atoms, an alkoxy group containing 1-10 carbon atoms, a phenyl group or a cumyl group; R3 is hydrogen, methyl, ethyl, propyl, isopropyl or a halogen; M is a pentavalent transition metal of the fifth subgroup, vanadium, niobium or tantalum; and X is a halogen, an alkyl group, a silane group or a benzyl group.
[0053] In some preferred embodiments of the present invention, R1 is preferably tert-butyl, tert-amyl, phenyl, 3,5-di-tert-butylphenyl, carbazolyl, adamantyl, cumyl or trityl; R2 is preferably methyl, ethyl, isopropyl, tert-butyl, tert-amyl, tert-octyl, methoxy or cumyl; R3 is preferably hydrogen, methyl, isopropyl or halogen; M is preferably the fifth subgroup pentavalent transition metal vanadium (V); X is preferably halogen or alkoxy.
[0054] The following nine complexes (C1-C9) are preferred among the OP bidentate fifth subgroup pentavalent metal complexes, and their specific structural formulas are as follows:
[0055]
[0056] The general structural formula of the ligand in the OP bidentate fifth subgroup pentavalent metal complex is as follows:
[0057] Wherein, R1 is an alkyl group containing 1-10 carbon atoms, an alkoxy group containing 1-10 carbon atoms, a phenyl group, a phenyl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a triphenylmethyl group; R2 is an alkyl group containing 1-10 carbon atoms, an alkoxy group containing 1-10 carbon atoms, a phenyl group or a cumyl group. The following 9 structures (L1-L9) are preferred:
[0058]
[0059] The method for preparing the OP bidentate fifth subgroup pentavalent metal complex comprises the following steps:
[0060] 1) A phenolic compound and 3,4-dihydropyran are used as raw materials, a condensation reaction is carried out under the catalysis of a catalyst, pyridinium p-toluenesulfonate, a saturated NaCl solution and a NaOH solution are added to the reactant for acid-base neutralization, an organic phase is separated and retained, the organic phase is washed with a saturated NaCl solution, dried, filtered, and rotary evaporated, and then anhydrous methanol is added thereto, stirred until a large amount of white precipitates are precipitated, filtered, and the filter cake is washed with anhydrous methanol to obtain a white solid, and the solvent is drained to obtain a white powder;
[0061] The phenolic compound is a known raw material in the prior art and can be directly purchased or synthesized using conventional methods. The preparation method of the compound is not used as a consideration criterion for examining the creativity of the present invention, and it only needs to be able to be successfully prepared.
[0062] 2) under a nitrogen atmosphere, the white powder is added to tetrahydrofuran (THF), the obtained solution is subjected to a metalation reaction with n-butyl lithium to generate a lithiated intermediate; the lithiated intermediate is reacted with diphenylphosphine chloride (Ph2PCl) to form a phosphorus compound, water is added to quench the reaction, the THF solvent is removed by rotary evaporation, CH2Cl2 is added to dissolve, a saturated NaCl solution is added thereto, the organic phase is separated and retained, the organic phase is washed with a saturated NaCl solution, dried, filtered, the filtrate is concentrated, anhydrous methanol is subsequently added to the reaction bottle, ultrasonically shaken, a white powder is precipitated, and filtered to obtain a compound;
[0063] 3) dissolving the compound in CH2Cl2, adding water and concentrated hydrochloric acid to carry out hydrolysis reaction, adding saturated NaCl solution after the reaction is complete, then dropping NaHCO3 solution to adjust pH=7, separating and retaining the organic phase, washing the organic phase with saturated NaCl solution, drying, filtering, rotary evaporation, and purifying the crude product by column chromatography (ethyl acetate: petroleum ether=1:50) to obtain the ligand;
[0064] 4) under an inert atmosphere, adding a fifth subgroup pentavalent transition metal compound (vanadium, niobium or tantalum) to dry benzene, stirring at room temperature to obtain a solution;
[0065] 5) The ligand prepared in step 3) is added in the form of powder to the solution obtained in step 4), triethylamine is added, the mixture is stirred at room temperature, filtered, concentrated, and stirred after adding n-hexane. The precipitated solid is filtered and dried to obtain a metal complex.
[0066] The OP bidentate fifth subgroup pentavalent metal complex can be used as a catalyst to catalyze the copolymerization of ethylene and norbornene. In the copolymerization, the main catalyst is the OP bidentate fifth subgroup pentavalent metal complex, and the cocatalyst is an alkylaluminoxane, a modified alkylaluminoxane (purchased from Nouryon), a haloalkylaluminum or a mixture of an alkylaluminum and a boron agent. The cocatalyst is preferably diethylaluminum chloride, monoethylaluminum dichloride or methylaluminoxane, more preferably diethylaluminum chloride.
[0067] In some preferred embodiments of the present invention, the molar ratio of the metal in the main catalyst to the aluminum in the co-catalyst is 1:(5-10000), preferably 1:(100-5000); the molar ratio of the metal in the main catalyst to the boron in the co-catalyst is 1:(0-2), that is, the boron agent may not be added; in the copolymerization reaction, the pressure of ethylene is 0.1-10MPa, preferably 0.1-1.0MPa.
[0068] The OP bidentate fifth subgroup pentavalent metal complex can also be used as a catalyst to catalyze the copolymerization of ethylene and a hydroxyl-containing polar monomer. In the copolymerization, the main catalyst is the OP bidentate fifth subgroup pentavalent metal complex, and the cocatalyst is an alkylaluminoxane, a modified alkylaluminoxane, a haloalkylaluminum, or a mixture of an alkylaluminum and a boron agent. The cocatalyst is preferably diethylaluminum chloride.
[0069] In some preferred embodiments of the present invention, the molar ratio of the metal in the main catalyst to the aluminum in the co-catalyst is 1:(5-10000), preferably 1:(100-5000); the molar ratio of the metal in the main catalyst to the boron in the co-catalyst is 1:(0-2), that is, the boron agent may not be added, preferably 1:1; in the copolymerization reaction, the pressure of ethylene is 0.1-10MPa, preferably 0.1-1.0MPa.
[0070] In the application process of the OP bidentate fifth subgroup pentavalent metal complex in catalyzing the copolymerization of ethylene and hydroxyl-containing polar monomers, the hydroxyl-containing polar monomers need to be pretreated with part of the co-catalyst in advance, and the pretreated product is then reacted with the main catalyst and the remaining co-catalyst. The molar ratio of the hydroxyl-containing polar monomer to part of the co-catalyst is (1.0-1.2):1, preferably 1:1. In the embodiment, the amount of the co-catalyst used for pre-treating the polar monomer is combined with the co-catalyst that plays a catalytic role.
[0071] The technical solution of the present invention is further described by way of examples. In the following examples, the preferred ligands L1-L9 are used as examples for experiments, and the corresponding metal complexes are C1-C9.
[0072] Example 1
[0073] A ligand (L1-L9) of an OP bidentate fifth subgroup pentavalent metal complex is prepared in the following manner:
[0074]
[0075] (1) Preparation of compound (B): Phenolic compound (A) (112 mmol, eq=1.0), pyridinium p-toluenesulfonate (PPTS, 5.6 mmol, eq=0.05) and CH2Cl2 (300 mL) were added to a 500 mL Schlenck bottle in sequence. The reaction bottle was placed in an ice-water bath and stirred. After 10 min, 3,4-dihydropyran (DHP, 168 mmol, eq=1.5) was added dropwise. After 10 min, the ice-water bath was removed and the reaction was continued for 3 hours. h; saturated NaCl solution (100 mL) and NaOH solution (50 mL, 1 mol / L) were added to the reaction flask in sequence, stirred for 10 min, separated and the organic phase was retained, the organic phase was washed 3 times with saturated NaCl solution, then anhydrous magnesium sulfate was added thereto for drying, filtered, most of the solvent was removed by rotary evaporation, anhydrous methanol (200 mL) was added thereto, and rapidly stirred for 20 min to precipitate a large amount of white precipitate, filtered, and the filter cake was washed 2 times with anhydrous methanol to obtain a white solid, and the solvent was drained to obtain a white powder (B);
[0076] (2) Preparation of compound (C): Compound (B) (34 mmol, eq=1.00) was added to a 200 mL Schlenck bottle, replaced with N2 atmosphere, and dry THF (120 mL) was introduced to dissolve it. The reaction bottle was placed in an ice-water bath and stirred. After 10 min, n-butyl lithium (37.4 mmol, eq=1.10) was dropped into it. The ice-water bath was removed and the temperature was raised to room temperature to continue the reaction for 5 h. The reaction bottle was placed in an ice-water bath again to cool, and Ph2PCl (39 mmol, eq=1.00) was added dropwise. q=1.15), remove the low temperature, warm to room temperature and react for 12h; add 1mL of water to the reaction bottle to quench the reaction, then remove the THF solvent by rotary evaporation, add CH2Cl2 (150mL) to dissolve, add saturated NaCl solution (100mL) thereto, separate the liquids and retain the organic phase, wash the organic phase with saturated NaCl solution 3 times, then add anhydrous sodium sulfate to dry, filter, concentrate the filtrate to 20mL, then add anhydrous methanol (150mL) to the reaction bottle, ultrasonically shake, precipitate white powder, and filter to obtain compound (C);
[0077] (3) Preparation of ligand (L): Compound (C) was dissolved in CH2Cl2 (150 mL), and then water (5 mL) and concentrated hydrochloric acid (2 mL) were added thereto. The reaction was stirred at room temperature and followed by TLC. After the reaction was completed, saturated NaCl solution (100 mL) was added thereto, and then NaHCO3 solution (2 mol / L) was added dropwise thereto to adjust the pH to 7. The organic phase was separated and retained. The organic phase was washed three times with saturated NaCl solution, and then anhydrous sodium sulfate was added thereto for drying. The mixture was filtered and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography (ethyl acetate: petroleum ether = 1:50) to obtain ligand (L).
[0078] When the phenolic compound (A) is 2-cumyl-4-methoxyphenol; 2-cumyl-4-tert-butylphenol; 2-cumyl-4-tert-octylphenol; 2-adamantyl-4-tert-butylphenol; 2-carbazolyl-4-tert-butylphenol; 2-trityl-4-tert-butylphenol; 2-trityl-4-tert-butylphenol; 2-(3,5-di-tert-butyl)phenyl-4-tert-butylphenol; 2,4-di-tert-amylphenol; and 2,4-di-tert-butylphenol, the corresponding ligands L1-L9 are obtained, and the synthesis and purification processes of the ligands L1-L9 are completely consistent with the methods described in (1), (2) and (3) above. The compounds (B) and (C) containing different substituent structures are all obtained by recrystallization from CH2Cl2 / methanol.
[0079] The experimental results of ligands L1-L9 are as follows:
[0080] L1: colorless crystalline solid, yield: 78.5%. 1 H NMR (400MHz, CDCl3) δ7.33-7.15(m,15H,Ar-H),7.09(d,J=2.9Hz,1H,Ar-H),6.16(dd,J =4.5,3.0Hz,1H,Ar-H),4.69(s,1H,-OH),3.57(s,3H,-OCH3),1.68(s,6H,Cumyl-CH3); 31 P NMR(162MHz, CDCl3)δ-18.44(s);
[0081] L2: colorless crystalline solid, yield: 69.7%. 1H NMR (400MHz, CDCl3) δ7.50 (d, J=2.3Hz, 1H, Ar-H), 7.31-7.21 (m, 14H, Ar-H), 7.18 (ddd, J=8.5, 6.0, 2.9Hz, 1H, Ar- H),6.66(dd,J=5.6,2.4Hz,1H,Ar-H),5.04(d,J=1.1Hz,1H,-OH),1.69(s,6H,Cumyl-CH3),1.17(s,9H,-C(CH3)3); 31 P NMR (162MHz, CDCl3) δ-19.18 (d, J=6.7Hz);
[0082] L3: white powder, yield: 80.9%. 1 H NMR (400MHz, CDCl3) δ7.48 (d, J=2.2Hz, 1H, Ar-H), 7.31-7.21 (m, 14H, Ar-H), 7.18 (dt, J=8.7, 4.4Hz, 1H, Ar-H), 6.63 (dd, J=5.4, 2.3Hz,1H,Ar-H),5.12(s,1H,-OH),1.69(s,6H,Cumyl-CH3),1.54(s,2H,-CH2-),1.19(s,6H,-C(CH3)2),0.66(s,9H,-C(CH3)3); 31 P NMR(162MHz, CDCl3)δ-20.43(s);
[0083] L4: white powder, yield: 75.2%. 1 H NMR (400MHz, CDCl3) δ7.35-7.29 (m, 10H, Ar-H), 6.86 (dd, J = 5.8, 2.4Hz, 1H, Ar-H), 6.69 (d, J = 10. 0Hz,1H,Ar-H),2.15(s,6H,Ad-H),2.07(s,3H,Ad-H),1.77(s,6H,Ad-H),1.15(s,9H,-C(CH3)3); 31 P NMR(162MHz, CDCl3)δ-29.84(s);
[0084] L5: white powder, yield: 82.1%. 1H NMR (400MHz, CDCl3) δ8.13 (d, J=7.7Hz, 2H, Ar-H), 7.47-7.35 (m, 13H, Ar-H), 7.29 (t, J=7.3Hz, 2H, Ar-H), 7.19(d,J=8.1Hz,2H,Ar-H),6.98(dd,J=5.7,2.4Hz,1H,Ar-H),5.47(s,1H,-OH),1.15(s,9H,-C(CH3)3); 31 PNMR (162MHz, CDCl3) δ-18.87 (d, J=6.2Hz);
[0085] L6: white powder, yield: 78.5%. 1 H NMR (400MHz, CDCl3) δ7.33-7.16(m,25H,Ar-H),7.12(d,J=2.1Hz,1H,Ar-H),6.70-6.64(m,1H,Ar-H),4.82(s,1H,-OH),0.97(s,9H,-C(CH3)3); 31 PNMR (162MHz, CDCl3) δ-15.68 (d, J=6.1Hz);
[0086] L7: white powder, yield: 75.4%. 1 H NMR (400MHz, CDCl3) δ7.44(s,1H,Ar-H),7.42-7.33(m,10H,Ar-H),7.32(d,J=1.2Hz,2H,Ar-H),7.29(d,J=2.3Hz, 1H,Ar-H),6.80(dt,J=12.1,6.1Hz,1H,Ar-H),5.89(s,1H,-OH),1.35(s,18H,-C(CH3)3),1.15(s,9H,-C(CH3)3); 31 PNMR (162MHz, CDCl3) δ-19.79 (dd, J=13.3, 6.5Hz);
[0087] L8: light blue crystalline solid, yield: 77.8%. 1H NMR (400MHz, CDCl3) δ7.25-7.18(m,9H,Ar-H),7.13(d,J=2.3Hz,1H,Ar-H),6.70(dd,J=5.8,2.4Hz,1H,Ar-H),6.52(d,J=10.0Hz,1H,Ar-H),1.77(d ,J=7.5Hz,2H,-CH2-),1.36(d,J=7.4Hz,2H,-CH2-),1.29(s,6H,-CH3),1.02(s,6H,-CH3),0.55(t,J=7.5Hz,3H,-CH3),0.49(t,J=7.4Hz,3H,-CH3); 31 PNMR(162MHz, CDCl3)δ-30.12(s);
[0088] L9: white powder, yield: 78.6%. 1 H NMR (400MHz, CDCl3) δ7.32-7.36(m,10H,Ar-H),6.86-6.88(m,1H,Ar-H),6.78-6.81(m,1H,Ar-H),1.41(s,9H,t-Bu),1.15(s,9H,t-Bu); 31 PNMR(162MHz,CDCl3)δ-28.97(s).
[0089] Example 2
[0090] An OP bidentate fifth subgroup pentavalent metal complex (C1-C9) is prepared in the following manner:
[0091]
[0092] Under an inert gas environment, V(N-2,6-Me2C6H3)Cl30.5000g (1.81mmol, eq=1.02) and 30mL of dry benzene were added to a 100mL Schlenk bottle in sequence, and the solid was dissolved by stirring at room temperature for 10min. Then, the ligands L1-L9 (1.77mmol, eq=1.00) powders were directly added to the above system, and the bottle wall was rinsed with 20mL of anhydrous benzene. After stirring for 10min, 0.30mL of triethylamine (2.13mmol, eq=1.20) was added thereto, and the reaction was stirred at room temperature overnight. The triethylamine hydrochloride was filtered out, and the filtrate was concentrated to 15mL, and then 30mL of n-hexane was added thereto, and the mixture was rapidly stirred for 20min. A large amount of solid was precipitated, and the metal complexes C1-C9 were obtained by filtering and drying.
[0093] The experimental results of metal complexes C1-C9 are as follows:
[0094] C1: Brown crystalline complex, yield: 78.2%. 1 H NMR (400 MHz, C6D6) δ 7.49 - 7.39 (m, 6H, Ar-H), 7.25 (t, J = 7.8 Hz, 2H, Ar-H), 7.13 (d, J = 2.8 Hz, 1H, Ar-H), 7.03 (t, J = 7.4 Hz, 1H, Ar-H), 6.84 (dd, J = 8.6, 6.6 Hz, 2H, Ar-H), 6.77 (t, J = 6.7 Hz, 4H, Ar-H), 6.53 (dd, J = 6.9, 2.8 Hz, 1H, Ar-H), 6.34 (t, J = 7.5 Hz, 1H, Ar-H), 6.24 (d, J = 7.6 Hz, 2H, Ar-H), 3.09 (s, 3H, -OCH3), 2.02 (s, 6H, Ar-CH3), 1.84 (s, 6H, Cumyl-CH3), see Figure 1 ;
[0095] C2: Dark green solid, yield: 74.5%. 1 H NMR (400 MHz, C6D6) δ 7.52 (td, J = 10.8, 4.6 Hz, 7H, Ar-H), 7.26 (t, J = 7.7 Hz, 2H, Ar-H), 7.19 - 7.16 (m, 1H, Ar-H), 7.03 (t, J = 7.3 Hz, 1H, Ar-H), 6.85 - 6.74 (m, 6H, Ar-H), 6.33 (t, J = 7.6 Hz, 1H, Ar-H), 6.24 (d, J = 7.5 Hz, 2H, Ar-H), 2.05 (s, 6H, Ar-CH3), 1.96 (s, 6H, Cumyl-CH3), 1.06 (s, 9H, -C(CH3)3);
[0096] C3: Yellow solid, yield: 65.2%. 1 H NMR (400 MHz, C6D6) δ 7.57 - 7.43 (m, 7H, Ar-H), 7.28 (t, J = 7.4 Hz, 2H, Ar-H), 7.06 (dd, J = 16.5, 7.6 Hz, 2H, Ar-H), 6.81 (dd, J = 13.2, 7.1 Hz, 6H, Ar-H), 6.33 (d, J = 6.8 Hz, 1H, Ar-H), 6.25 (d, J = 7.3 Hz, 2H, Ar-H), 2.06 (s, 6H, Ar-CH3), 1.95 (s, 6H, Cumyl-CH3), 1.47 (s, 2H, -CH2-), 1.10 (s, 6H, -C(CH3)2), 0.64 (s, 9H, -C(CH3)3);
[0097] C4: brown-grey solid, yield: 75.1%. 1 H NMR (400MHz, C6D6) δ7.56(dd,J=10.3,7.4Hz,5H,Ar-H),7.20(d,J=8.6Hz,1H,Ar-H),6.88-6.75(m,6H,Ar-H),6.35(t,J=7.5Hz,1H,Ar-H),6.25(d ,J=7.5Hz,2H,Ar-H),2.41(s,6H,Ar-CH3),2.20(s,9H,Ad-H),2.02(d,J=11.8Hz,3H,Ad-H),1.83(d,J=11.7Hz,3H,Ad-H),1.12(s,9H,-C(CH3)3);
[0098] C5: yellow solid, yield: 69.4%. 1 H NMR (400MHz, CDCl3) δ8.13(d,J=7.6Hz,2H,Ar-H),7.74(d,J=2.1Hz,1H,Ar-H),7.63(dd,J=10.8,7.9Hz,4H,Ar-H),7.49-7.42(m,4H,Ar-H),7.37(d,J=9. 2Hz,5H,Ar-H),7.29(dd,J=7.3,5.0Hz,5H,Ar-H),6.72(t,J=7.6Hz,1H,Ar-H ),6.61(d,J=7.5Hz,2H,Ar-H),2.02(s,6H,Ar-CH3),1.29(s,9H,-C(CH3)3);
[0099] C6: orange solid, yield: 80.9%. 1 H NMR (400MHz, C6D6) δ7.94(d,J=2.1Hz,1H,Ar-H),7.65(d,J=7.6Hz,6H,Ar-H),7.60( ddd,J=11.0,7.3,2.0Hz,4H,Ar-H),7.29(dd,J=7.1,2.1Hz,1H,Ar-H),7.18-7.13(m ,6H,Ar-H),6.95(t,J=7.4Hz,3H,Ar-H),6.87(d,J=4.3Hz,6H,Ar-H),6.37-6.32(m, 1H, Ar-H), 6.27 (d, J = 7.6Hz, 2H, Ar-H), 1.84 (s, 6H, Ar-CH3), 1.05 (s, 9H, -C (CH3) 3);
[0100] C7: dark green solid, yield: 73.8%. 1H NMR (400MHz, C6D6) δ8.04(s,2H,Ar-H),7.82(s,1H,Ar-H),7.66(s,1H,Ar-H),7.57(dd,J=10.6,7.9Hz,4H,Ar-H),7.27(d,J=5.5Hz,1H,Ar-H),6.83(dt ,J=13.6,6.9Hz,6H,Ar-H),6.36-6.28(m,1H,Ar-H),6.23(d,J=7.5Hz,2H,A r-H),2.23(s,6H,Ar-CH3),1.51(s,18H,-C(CH3)3),1.08(s,9H,-C(CH3)3);
[0101] C8: gray-green solid, yield: 72.3%. 1 H NMR(400MHz,C6D6)δ7.55(dd,J=10.5,7.7Hz,4H,Ar-H),7.44(d,J=1.8Hz,1H,Ar-H),7.10(dd ,J=7.1,1.9Hz,1H,Ar-H),6.80(dd,J=16.9,8.3Hz,6H,Ar-H),6.34(d,J=7.9Hz,1H,Ar-H),6.2 6(d,J=7.2Hz,2H,Ar-H),2.21(s,6H,Ar-CH3),2.13(s,2H,-CH2-),1.56(s,6H,-CH3),1.42-1. 37(m,2H,-CH2-),1.05(s,6H,-CH3),0.77(t,J=7.4Hz,3H,-CH3),0.55(t,J=7.4Hz,3H,-CH3);
[0102] C9: dark green solid, yield: 76.2%. 1 H NMR (400MHz, C6D6) δ7.56 (t, J=9.1Hz, 5H, Ar-H), 7.19 (d, J=7.3Hz, 1H, Ar-H), 6.82 (dd, J=16.0, 6.8Hz, 6H, Ar-H), 6.40 -6.33(m,1H,Ar-H),6.25(d,J=7.2Hz,2H,Ar-H),2.19(s,6H,Ar-CH3),1.61(s,9H,-C(CH3)3),1.08(s,9H,-C(CH3)3).
[0103] Application Example 1
[0104] Example 2 The C1-C9 prepared in Example 2 catalyzes the polymerization of ethylene at normal pressure (0.1 MPa): The polymerization reaction is carried out in a 200 mL glass reaction bottle. The glass reaction bottle equipped with a mechanical stirrer is heated to 120°C, vacuumed for 1 hour, and filled with 0.1 MPa ethylene gas. The vacuumization and ethylene gas replacement are continuously repeated 3 times to adjust the system to the temperature conditions required for polymerization. A toluene solution containing a co-catalyst and a reactivating agent (ethyl trichloroacetate) is added to the polymerization reaction bottle (the final total volume of the solution is 80 mL), and the temperature is kept for a period of time until the temperature is constant (the specific temperature selection is shown in Table 1), 0.1 MPa ethylene gas is introduced, and ethylene is allowed to reach a dissolution equilibrium for 10 minutes, and then the main catalyst (C1-C9 prepared in Example 2) is added and stirred for reaction. After the polymerization reaction is completed, the residual ethylene gas is released, the reaction bottle is opened, and the obtained polymerization reaction mixture is poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15 minutes, filtered, and the polymer product is dried in a vacuum oven. Weigh its mass, and measure its molecular weight, molecular weight distribution and melting point.
[0105] a Polymerization conditions: The amount of the main catalyst C1-C9 was 1 μmol, the co-catalyst was diethylaluminum chloride (Et2AlCl), the amount of which is shown in Table 1, the reactivating agent was ethyl trichloroacetate: 0.3 mmol, the polymerization pressure was 0.1 MPa, and the polymerization time was 10 min. The results are shown in Table 1.
[0106] Table 1 Data of ethylene homopolymerization at normal pressure catalyzed by selected main catalysts a
[0107]
[0108] Note: c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC. d Tm (melting point) was measured by DSC; e 15: The polymerization time is 60 min; Al / M refers to the molar ratio of aluminum in the co-catalyst to metal vanadium in the main catalyst.
[0109] Application Example 2
[0110] The C1, C8, and C9 prepared in Example 2 catalyze the high-pressure (0.5-1.0 MPa) polymerization of ethylene: The polymerization reaction is carried out in a 250 mL stainless steel autoclave. A glass reaction bottle equipped with a mechanical stirrer is heated to 200° C. and vacuumed for 1 h. The system is adjusted to the temperature conditions required for polymerization. 0.1 MPa of ethylene gas is introduced, and vacuumization and ethylene gas replacement are continuously performed 3 times to adjust the system to the temperature conditions required for polymerization. Toluene purified with a co-catalyst (in sequence numbers 7-11 in Table 2, the toluene is replaced with other solvents to explore the influence of solvent differences on the effect) and a reactivating agent (ethyl trichloroacetate) are added to the polymerization reaction bottle. The total volume is 200 mL. The temperature is kept for a period of time until the temperature is constant (the specific temperature selection is shown in Table 2), and ethylene gas of a certain pressure (specific pressure is shown in Table 2) is introduced. Wait for 10 min to allow ethylene to reach a dissolution equilibrium, and then the main catalyst (C1, C8, and C9 prepared in Example 2) is added and stirred for reaction. After the polymerization reaction is completed, the residual ethylene gas is released, the reactor is opened, and the obtained polymerization reaction mixture is poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15 minutes, filtered, and the polymer product is dried in a vacuum oven. Weigh its mass, and measure its molecular weight, molecular weight distribution and melting point.
[0111] a Polymerization conditions: the cocatalyst is diethylaluminum chloride (Et2AlCl), the dosage is 2 mmol, the reactivating agent is ethyl trichloroacetate: 0.3 mmol, and the polymerization time is 10 min. The results are shown in Table 2.
[0112] Table 2 Data of high pressure homopolymerization of ethylene catalyzed by selected main catalysts a
[0113]
[0114]
[0115] Note: c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC. d Tm (melting point) was measured by DSC; e 7: dichloromethane solvent; f 8: n-hexane solvent; h 9: Toluene solvent; i 10: xylene solvent; j 11: Octane.
[0116] Application Example 3
[0117] Example 2 The prepared C1-C9 catalyzes the copolymerization of ethylene and norbornene (NBE): The polymerization reaction is carried out in a 250mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring is heated to 200°C, vacuumed for 1h, the system is adjusted to the temperature conditions required for polymerization, 0.1MPa of ethylene gas is charged, and a toluene solution containing a certain amount of diethylaluminum chloride, a reactivating agent (ethyl trichloroacetate) and a certain concentration of norbornene (the final total volume of the solution is 200mL) is added to the polymerization autoclave, and the temperature is kept for a period of time until the temperature is constant, and 0.5MPa of ethylene gas is passed, and 10min is waited for ethylene to reach a dissolution equilibrium, and then the main catalyst is added and stirred for a period of time. After the polymerization reaction is completed, the residual ethylene gas is released, the reactor is opened, and the obtained polymerization reaction mixture is poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15min, filtered, and the polymer product is dried in a vacuum oven. Weigh its mass, measure its molecular weight and molecular weight distribution, and measure its comonomer insertion rate by high-temperature carbon spectrum.
[0118] a Polymerization conditions: the amount of main catalyst C1-C9 is 1 μmol, the co-catalyst is Et2AlCl: 2 mmol, the reactivating agent is ethyl trichloroacetate: 0.3 mmol, the polymerization temperature is 50°C, the polymerization pressure is 0.50 MPa, and the polymerization time is 10 min. The results are shown in Table 3. The nuclear magnetic resonance carbon spectrum of the copolymer of ethylene and norbornene under the catalytic action of catalyst C1 (C1 of sequence number 5 in Table 3) is shown in Figure 2 (The sum of x+y in the figure is 100%).
[0119] Table 3 Data of copolymerization of ethylene and NBE catalyzed by selected main catalysts a
[0120]
[0121] Note: c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC. d The NBE insertion rate is given by 13 Measured by CNMR.
[0122] Application Example 4
[0123] The C1, C3 and C5 prepared in Example 2 catalyze the copolymerization of ethylene and polar monomers:
[0124] The polymerization reaction was carried out in a 250mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was heated to 200℃, vacuumed for 1h, the system was adjusted to the required temperature conditions for polymerization, 0.1MPa of ethylene gas was charged, and a toluene solution containing a certain amount of diethylaluminum chloride and a certain concentration of polar monomer (5-norbornene-2-methanol) pretreated with diethylaluminum chloride and a reactivator (ethyl trichloroacetate) was added to the polymerization autoclave (the final total volume of the solution was 60mL). The temperature was kept for a period of time until the temperature was constant, 0.5MPa of ethylene gas was passed, and ethylene was allowed to reach a dissolution equilibrium for 10min, and then the main catalyst was added and stirred for a period of time. After the polymerization reaction was completed, the residual ethylene gas was released, the reactor was opened, and the obtained polymerization reaction mixture was poured into a mixed solution of 3M hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 15min, filtered, and the polymer product was dried in a vacuum oven. Weigh its mass, measure its molecular weight and molecular weight distribution, and measure the comonomer insertion rate by high-temperature hydrogen spectrum.
[0125] The molar ratio of diethylaluminum chloride used for pretreating polar monomers to polar monomers is 1:1, and the pretreatment time is 20 min. The amount of co-catalyst added in Table 4 is the total amount of diethylaluminum chloride added to the reaction system, excluding the remaining amount used for pretreating polar monomers to play a co-catalyst role.
[0126] a Polymerization conditions: the amount of the main catalyst is 1 μmol, the co-catalyst is Et2AlCl, the polymerization temperature is 50°C, the reactivating agent is ethyl trichloroacetate: 0.3 mmol, the polymerization pressure is 0.50 MPa, and the polymerization time is 10 min. The results are shown in Table 4. The nuclear magnetic resonance hydrogen spectrum of the copolymer of ethylene and 5-norbornene-2-methanol under the catalytic action of catalyst C1 (C1 of sequence number 3 in Table 4) is shown in Figure 3 (The sum of x+y in the figure is 100%).
[0127] Table 4 Data of copolymerization of ethylene and 5-norbornene-2-methanol catalyzed by selected main catalysts a
[0128]
[0129] Note: c Mw (molecular weight), c PDI (molecular weight distribution) is measured by high temperature GPC, and the monomer insertion rate is measured by 1 Measured by HNMR.
[0130] It can be seen from the above experimental results that the new OP bidentate fifth subgroup pentavalent metal complex provided by the present invention catalyzes ethylene homopolymerization, and the activity can reach up to 262.40×10 6g / (molV·h), under 1.0MPa ethylene pressure, the activity can reach up to 446.47×10 6 g / (molV·h), at 120℃, the activity can still reach 1.28×10 6 g / (molV·h); when polymerized at normal pressure, it still has catalytic activity when the reaction is carried out for 60 minutes; the activity of catalyzing the copolymerization of ethylene and norbornene can reach 112.17×10 6 g / (molV·h), and the molecular weight of the obtained polymer was as high as 49.6×10 4 g / mol, the highest molar insertion rate of norbornene was 52.3%; the activity of catalyzing the copolymerization of ethylene and 5-norbornene-2-methanol was 8.56×10 6 g / (molV·h), and the molecular weight of the obtained polymer was as high as 25.6×10 4 g / mol, and the highest molar insertion rate of 5-norbornene-2-methanol was 4.2%.
[0131] It can be seen from the above embodiments that the present invention provides a novel OP bidentate fifth subgroup pentavalent metal complex, which has high catalytic activity, long service life, and good temperature resistance when catalyzing ethylene polymerization, and can maintain a high catalytic activity under 120°C; it catalyzes the copolymerization of ethylene and norbornene, showing ultra-high activity, and the molecular weight and insertion rate of the obtained polymer are very high; it catalyzes the copolymerization of ethylene and 5-norbornene-2-methanol, has high catalytic activity, and the molecular weight and comonomer content are also very high, and a functionalized polymer product is obtained.
[0132] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. An OP bidentate fifth subgroup pentavalent metal complex, characterized in that: It has the following general structural formula: Wherein, R1 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, a phenyl group, a phenyl group containing a substituent, a carbazolyl group, an adamantyl group, a cumyl group, a diphenylmethyl group or a triphenylmethyl group; R2 is an alkyl group containing 1 to 10 carbon atoms, an alkoxy group containing 1 to 10 carbon atoms, a phenyl group or a cumyl group; R3 is hydrogen, methyl, ethyl, propyl, isopropyl or halogen; M is vanadium, a pentavalent transition metal of the fifth subgroup; X is halogen, alkyl or benzyl.
2. A method for preparing the OP bidentate fifth subgroup pentavalent metal complex as claimed in claim 1, characterized in that: The following steps are involved: Under the catalysis of pyridinium p-toluenesulfonate, phenolic compounds and 3,4-dihydropyran undergo condensation reaction, and the obtained product is post-treated to obtain a white powder; In a nitrogen atmosphere, the white powder is added to THF, and the obtained solution is subjected to a metalation reaction with n-butyl lithium to generate a lithiated intermediate; the lithiated intermediate is reacted with diphenylphosphine chloride to form a phosphorus compound, water is added to quench the reaction, and a compound is obtained through post-treatment; The compound is dissolved in CH2Cl2, water and concentrated hydrochloric acid are added to perform a hydrolysis reaction, and a ligand is obtained through post-treatment; Under an inert atmosphere, a pentavalent transition metal compound of the fifth subgroup is added to dry benzene, and stirred at room temperature to obtain a solution; The ligand is added to the solution in the form of powder, triethylamine is added, the mixture is stirred at room temperature, filtered, concentrated, and stirred after adding n-hexane. The precipitated solid is filtered and dried to obtain a metal complex.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the pyridinium p-toluenesulfonate, the phenolic compound and 3,4-dihydropyran is 5.6:112:168; The molar ratio of the white powder, n-butyl lithium and diphenylphosphine chloride is 34:37.4:
39.
4. Use of the OP bidentate fifth subgroup pentavalent metal complex as claimed in claim 1 in catalyzing the copolymerization of ethylene and norbornene.
5. The use according to claim 4, characterized in that: In the copolymerization reaction, the OP bidentate fifth subgroup pentavalent metal complex is used as the main catalyst, and the alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as the co-catalyst.
6. The use according to claim 5, characterized in that: The molar ratio of the metal in the main catalyst to the aluminum in the co-catalyst is 1:(5-10000); During the copolymerization reaction, the ethylene pressure is 0.1-10 MPa.
7. Use of the OP bidentate fifth subgroup pentavalent metal complex as claimed in claim 1 in catalyzing the copolymerization of ethylene and a hydroxyl-containing polar monomer.
8. The use according to claim 7, characterized in that: In the copolymerization reaction, the OP bidentate fifth subgroup pentavalent metal complex is used as the main catalyst, and the alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum or a mixture of alkylaluminum and a boron agent is used as the co-catalyst.
9. The use according to claim 8, characterized in that: The molar ratio of the metal in the main catalyst to the aluminum in the co-catalyst is 1:(5-10000); during the copolymerization reaction, the pressure of ethylene is 0.1-10MPa.
Citation Information
Patent Citations
Vanadium complex catalyst containing phenoxy ligand and preparation method and application of vanadium complex catalyst
CN111848669A
Transition metal complex, olefin polymerization catalyst, and method for manufacturing olefin polymer
JP2004182659A